2017
DOI: 10.1038/srep43923
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of age on pro-inflammatory miRNAs contained in mesenchymal stem cell-derived extracellular vesicles

Abstract: Stem cells possess significant age-dependent differences in their immune-response profile. These differences were analysed by Next-Generation Sequencing of six age groups from bone marrow mesenchymal stem cells. A total of 9,628 genes presenting differential expression between age groups were grouped into metabolic pathways. We focused our research on young, pre-pubertal and adult groups, which presented the highest amount of differentially expressed genes related to inflammation mediated by chemokine and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 50 publications
7
65
0
Order By: Relevance
“…MiR‐21 is one of the most common anti‐inflammatory miRNAs (Sheedy, ). It is a negative regulator of TLR‐4 signaling (Fafian‐Labora et al, ), able to downregulate the expression of two essential mediators for NF‐κB activation, the TLR‐4 adaptor protein MyD88 and its downstream target IL1 receptor‐associated kinase (IRAK) (Y. Chen et al, ). In addition, miR‐21 targets programmed cell death protein 4 (PDCD4) (Sheedy et al, ) and the apoptotic protein FasL (L. Zhang, Dong, Li, Hong, & Wei, ) protecting against microglia‐mediated neuron cell death in hypoxic/ischemic conditions (L. Zhang et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…MiR‐21 is one of the most common anti‐inflammatory miRNAs (Sheedy, ). It is a negative regulator of TLR‐4 signaling (Fafian‐Labora et al, ), able to downregulate the expression of two essential mediators for NF‐κB activation, the TLR‐4 adaptor protein MyD88 and its downstream target IL1 receptor‐associated kinase (IRAK) (Y. Chen et al, ). In addition, miR‐21 targets programmed cell death protein 4 (PDCD4) (Sheedy et al, ) and the apoptotic protein FasL (L. Zhang, Dong, Li, Hong, & Wei, ) protecting against microglia‐mediated neuron cell death in hypoxic/ischemic conditions (L. Zhang et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…Similar to the inducing effect in UC‐MSCs, miR‐301a increased NFκB activation and inflammatory gene expression in TLR 3‐, 4‐, and 9‐activated macrophages, which was mediated by inhibition of NFκB repressing factor . In another study, LPS stimulation upregulated miR‐21‐5p whose inhibition decreased TLR4 and the downstream cytokine (IL‐6, IL‐1β) gene expression in BM‐MSCs . miR‐21 suppression upregulated Wnta transcription, implying that the enhancing effect of miR‐21 on TLR signaling is mediated by negative regulation of Wnt.…”
Section: Micro‐rnas As Novel Modulators Of Tlr‐mediated Response In Mscsmentioning
confidence: 81%
“…From a clinical standpoint, similar concerns regarding inter‐donor variability and effects of aging and culture expansion on the therapeutic efficacy of MSCs may also apply to the miRNAs derived from these MSCs. In a recent study, Fafián‐Labora et al used NGS and compared the miRNA signature of EVs derived from BM‐MSCs in six age groups of mice, and showed that miR‐21‐5p was highly expressed in pre‐pubertal animals relative to other age groups. MSCs from the pre‐pubertal group displayed the highest level of inflammatory response after LPS treatment, and inhibition of miR‐21‐5p in those cells repressed TLR4 mRNA and protein, as well as danger signal mRNA (HMGB1, S100A4, S100A6) and cytokines (IL‐1β, IL‐6).…”
Section: Tlr‐mirna Regulatory Axis In Mscs: a Therapeutic Perspectivementioning
confidence: 99%
“…Increase of EV production is a general feature in aged and senescence-induced cells as shown by several studies as early as 2008 (Lehmann et al, 2008;Beer et al, 2015;Takasugi et al, 2017). Accordingly, the production of EVs by MSCs increases with donor age and late passage cultures (Fafian-Labora et al, 2017Lei et al, 2017). The release of EVs from senescent cells is at least partially dependent on p53 and its downstream target gene tumor suppression-activated pathway 6 (TSAP6).…”
Section: Characteristics and Function Of Evs From Senescent Or Aged Mscsmentioning
confidence: 97%
“…These miRNAs called inflammamiRs regulate the main age-related processes: DDR, oxidative stress, proteotoxic stress, senescence or mitochondrial dysfunction (for a review, see Prattichizzo et al, 2017). A panel of inflammamiRs commonly identified in distinct cell types includes miR-19b, miR-20a, miR-21, miR-126, miR-146a, and miR-155. In MSC-EVs, expression of several miRNAs is modulated with increasing age (for review, see Fafian-Labora et al, 2017). A decreased expression of a number of miRNAs was observed in MSC-EVs from old versus young rats (Wang et al, 2015).…”
Section: Characteristics and Function Of Evs From Senescent Or Aged Mscsmentioning
confidence: 99%